(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
The history of the traditional uncut Indian garment, the Sari, can be traced back to the Indus Valley Civilization, which emerged during 2800-1800 BC in northwest India. Mention of the sari evolved from śāṭikā in Sanskrit, appearing in Hindu and Páli Buddhist literature during the 6th century BC as a female garment. The study relied on a random sample of 50 women, most of whom were working women, to assess their opinions on wearing a sari and to explore the various reasons that influence the purchase intention or frequency of use among Indian women. The study concluded that among women aged from less than 25 years old to 75 years old, most find pleasure in wearing the sari in various ways. The most important aspects are fabric purity and quality, while some women worried about movement/walking and repeated use. It is important to emphasize that the participants in this study appreciated the use of the sari and did not report significant problems regarding the way of wearing it in front of spectators. While 6% of women were unable to wear a sari, 96% said they would miss their sari if it went missing.